Penerapan Teknik dan Balutan Luka Modern untuk Mempercepat Penyembuhan Luka Infeksi Daerah Operasi (IDO) Paska Persalinan Sectio Caesaria - Idramsyah, Idramsyah; Dahrizal, Dahrizal; Husni, Husni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to provide an overview of the application of modern techniques and wound dressings to accelerate healing of surgical site infections (SSI) after caesarean section (SC) delivery. This descriptive case study method involved 2 patients who experienced surgical wound infections after SC delivery at the wound care clinic. Participants were given treatment for 4 weeks with 10-12 treatment visits. Planning with TIME management and using modern dressing. The results of the case study include procedures for washing the wound using irrigation techniques and gentle rubbing using 0.9% Nacl and non-toxic gentle antiseptic soap, followed by compression with polyhexamethyl biguanide (PHMB) solution. The procedure for removing dead tissue uses mechanical techniques using scissors, tweezers and gauze and is followed by autolysis debridement using zinc cream chitosan. The procedure provides a primary dressing in the form of silver alginate at the wound undermining, zinc cream chitosan and cadexomer iodine in the wound infection phase, and using zinc hyaluride acid cream in the wound proliferation phase with a secondary dressing of polyurethane foam and fixation with transparent film. Inflammation and infection in the wound area were controlled for 3 days, proliferation until the wound closed with epithelial tissue lasted for 4 weeks. Conclusion: the treatment techniques and wound dressing materials used in wound care can be adjusted to the condition of the wound and the patient's financial ability to prove effective in accelerating wound healing. Key Words: Modern Dressings, Surgical Site Infections, Cesarean Wounds, Surgical Wounds, Cesarean Delivery